Engineering osteogenic microenvironments by combination of multilayers from collagen type I and chondroitin sulfate with novel cationic liposomes. (June 2020) - Brito Barrera, Y.A.; Hause, G.; Menzel, M.; Schmelzer, C.E.H.; Lehner, E.; Mäder, K.; Wölk, C.; Groth, T.
Abstract: Cationic liposomes composed of a novel lipid (N-6-amino-1-[N-(9Z) -octadec9-enylamino] -1-oxohexan-(2S) -2-yl –N'- 2- [N, N-bis(2-aminoethyl) amino] ethyl -2-hexadecylpropandiamide) (OO4) and dioleoylphosphatidylethanolamine (DOPE) possess high amounts of amino groups and are promising systems for lipofection. Moreover, these cationic liposomes can also be used as a polycationic entity in multilayer formation using layer-by-layer technique (LbL), which is a method to fabricate surface coatings by alternating adsorption of polyanions and polycations. Since liposomes are suitable for endocytosis by or fusion with cells, controlled release of their cargo on site is possible. Here, a polyelectrolyte multilayer (PEM) system was designed of chondroitin sulfate (CS) and collagen type I (Col I) by LbL technique with OO4/DOPE liposomes embedded in the terminal layers to create an osteogenic microenvironment. Both, the composition of PEM and cargo of the liposomes were used to promote osteogenic differentiation of C2C12 myoblasts as in vitro model. The internalization of cargo-loaded liposomes from the PEM into C2C12 cells was studied using lipophilic (Rhodamine-DOPE conjugate) and hydrophilic (Texas Red–labeled dextran) model compounds. Besides, the use of Col I and CS should mimic the extracellular matrix of bone for future applications such as bone replacement therapies. Physicochemical studies of PEM were done to characterize the layer growth, thickness, and topography. The adhesion of myoblast cells was also evaluated whereby the benefit of a cover layer of CS and finally Col I above the liposome layer was demonstrated. As proof of concept, OO4/DOPE liposomes were loaded with dexamethasone, a compound that can induce osteogenic differentiation. A successful induction of osteogenic differentiation of C2C12 cells with the novel designed liposome-loaded PEM system was shown. These findings indicate that designed OH4/DOPE loaded PEMs have a high potential to be used as drug delivery or transfection system for implant coating in the field of bone regeneration and other applications. Graphical abstract: Image 1